Determination of Shelf Life of Herbal Products from the Combination of Stevia rebaudiana, Curcuma zanthorrhiza and Honey (Stekurmin MD) through the Accelerated Shelf Life Test (ASLT) Method - Yohanes Martono; Fidelia Novitasari; November Rianto Aminu (Jurnal Kimia Sains dan Aplikasi, 2020)
Stekurmin MD is a syrup preparation formulated from the extract of Stevia rebaudiana leaves, temu lawak (Curcuma zanthorrhiza), and honey. One of the active compounds in Stekurmin MD products is phenolic and flavonoid compounds in which the active phenolic and flavonoid compounds can be degraded during the storage period. This study aimed to determine the shelf life of Stekurmin MD products based on the degradation of phenolic compounds and flavonoids. The Accelerated Shelf Life Test (ASLT) method was used in determining the shelf life kinetics of this product. Phenolic and flavonoid concentrations were determined using the UV-Vis spectrophotometric method with the gallic acid standard for phenolic and quercetin standard for flavonoids. Degradation of phenolic and flavonoid compounds was determined every 7 days during 35 days of storage at 25, 35, 45, and 55°C ± 2°C. In natural ingredients, there is a multi-mechanism reaction. The shelf life of Stekurmin MD products based on the degradation of phenolic and flavonoid active ingredients at room temperature were 39.909 days and 23.53 hours, respectively.